The Changing Face of Audio-Media in India During Post Privatization Period:An Empirical Study - Das, J. K.; Kar, Ashutosh (Indian Journal of Marketing, 2009)
Privatization is the key word after liberalization. Every sector has tasted the success of privatization; broadcasting media is not an exception. The changing face of audio-media after privatization has been studied in this article. The study considers the different factors which are popularizing the audio-media among the respondents, contribution of FM channels towards teaching and social welfare, attitudinal change of the listeners, attitudinal change of business houses etc. The period of study is from 2007-2008.